2020
DOI: 10.3389/fpsyg.2020.00986
|View full text |Cite
|
Sign up to set email alerts
|

The Taste of Emotion: Metaphoric Association Between Taste Words and Emotion/Emotion-Laden Words

Abstract: According to the Conceptual Metaphor Theory, abstract concepts can be metaphorically associated with more concrete, physically embodied concepts, such as gustatory experience. Studies on taste-emotion metaphoric association reported that people associate love with sweet, jealousy with sour and bitter, and sadness with bitter. However, few studies have systematically examined the metaphoric association between taste and words referred to emotion (e.g., "sad") or emotion-laden concepts (e.g., "funeral"). In the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(25 citation statements)
references
References 36 publications
1
15
1
Order By: Relevance
“…This finding underscores the importance of hedonic valence as one of the core features of emotional experience (Russell, 2003;Barrett and Bliss-Moreau, 2009) and echoes the prior finding that hedonic valence and arousal represent a source of universal structure for emotion semantics (Jackson et al, 2019). We also found that the similarity of taste and emotion concepts was also significantly related to their similarity in valence, which accounted for nearly 30% of the variance in the distribution (see also Zhou and Tse, 2020). This relationship between valence and semantic similarity was also significantly greater between taste and emotion concepts than between color and emotion concepts.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…This finding underscores the importance of hedonic valence as one of the core features of emotional experience (Russell, 2003;Barrett and Bliss-Moreau, 2009) and echoes the prior finding that hedonic valence and arousal represent a source of universal structure for emotion semantics (Jackson et al, 2019). We also found that the similarity of taste and emotion concepts was also significantly related to their similarity in valence, which accounted for nearly 30% of the variance in the distribution (see also Zhou and Tse, 2020). This relationship between valence and semantic similarity was also significantly greater between taste and emotion concepts than between color and emotion concepts.…”
Section: Discussionsupporting
confidence: 85%
“…One limitation of the present study is that our behavioral data as well as the valence and arousal norms we employed in the analysis of this data ( Warriner et al, 2013 ) were both obtained from western, English-speaking populations. Taste–emotion metaphors are present across multiple languages, however (for example, see Zhou and Tse, 2020 ), implying the association between these two domains might be a universal feature of human language. Thus, it will be important for future studies to obtain more widespread cross-cultural measures of these norms and associations (see Jonauskaite et al, 2020 ) in order to verify their similarity across human languages (see Kemmerer, 2019 for an in-depth discussion of culture and conceptual structure).…”
Section: Discussionmentioning
confidence: 99%
“…To be more specific, I understand kuqing as an affective response of the bottom strata of Chinese society to their "bitter (ku 苦)" life experiences, and as a felt quality that provides clues as to how we exist. The directly corresponding word in English is "bitter emotion": it can be seen that both Chinese and English use taste words to describe emotions, and bitterness is usually associated with negative emotion/emotion-laden words, particularly with sadness and agony (Zhou & Tse, 2020). I argue that such an association between taste and emotion is not just metaphorical, but an embodied affective practice that is grounded in daily sensory experiences and the linguistic practices of a class divided China.…”
Section: The Affective Scenes Of Kuqingmentioning
confidence: 90%
“…However, if people apply typefaces already linked with specific tastes in the learning of linguistic and gustatory stimuli, the established connections between typefaces and tastes would influence the learning and test phases of linguistic forms and tastes. Furthermore, recent findings suggest that certain tastes (i.e., sweetness) may be linked with positive emotion words, while other tastes (i.e., bitterness, sourness, and spiciness) may be linked with negative emotion words [ 55 ].…”
Section: Discussionmentioning
confidence: 99%